Upaya Meningkatkan Keterampilan Berpikir Tingkat Tinggi Siswa SD melalui Model Problem Based Learning - Wahyu Amana Sulaiman; Yudha Febrianta (Universitas Pendidikan Indonesia (UPI), 2022)
Facing an increasingly complex and dynamic world, mastering High Order Thinking Skills is a must and is still a challenge for the world of education. This classroom action research aims to improve the high-level thinking skills of fifth-grade students at SD Negeri 1 Mandiraja Wetan through the Problem-Based Learning (PBL) model. The subjects of this study were all fifth-grade students at SD Negeri 1 Mandiraja Wetan. Data collection techniques using tests, non-tests, observation, and documentation. The validity of the data used technical triangulation, and the collected data was then analyzed using qualitative data analysis techniques, including data collection, data presentation, and conclusion drawing. The results of this study indicate that the use of the PBL model can improve the high-level thinking skills of fifth-grade students at SD Negeri 1 Mandiraja Wetan.